Growth, gas exchange and photochemical efficiency of the cowpea bean under salt stress and phosphorus fertilization - Sá, Francisco Vanies da Silva; Ferreira Neto, Miguel; Lima, Yuri Bezerra de; Paiva, Emanoela Pereira de; Prata, Rômulo Costa; Lacerda, Claudivan Feitosa; Brito, Marcos Eric Baborsa (Comunicata Scientiae, 2019)
Cowpea is widely cultivated in semiarid regions; however, these regions face serious problems with salinity of water and soil, thus constituting an abiotic stress that limits the development of this species. The objective of this study was to study the influence of phosphate fertilization on the morphophysiological components of cowpea plants irrigated with salinized water during the vegetative and reproductive phase. The research was carried out in a greenhouse from September to December 2015. A randomized complete block design with treatments arranged in a 5 x 3 factorial scheme with five replications was used. The factors consisted of the use of five levels of electrical conductivity of irrigation water: 0.5; 1.5; 2.5; 3.5 and 4.5 dS m-1 and three doses of phosphorus corresponding to 60%, 100% and 140% of the dose recommended for the culture that was 60 kg ha-1. The plants of cowpea cv. Paulistinha were cultivated in lysimeters with a capacity of 8 dm3. At 30 and 49 days after sowing, periods corresponding to the vegetative (V4) and reproductive (V8 / R1) phases of the culture were evaluated gas exchange, chlorophyll fluorescence and growth. The increase in the electrical conductivity of the water reduced the growth, the photochemical activity and the phytomass accumulation of the cowpea plants, independent of the phenological phase. The higher dose of simple superphosphate increased the growth and photosynthetic activity of cowpea, mainly in the reproductive phase; Independent of the salinity of irrigation water.